Radiometric Receiver for Passive Microwave Imaging System; MATEC Web of Conferences; Vol. 79 : Information-Measuring Equipment and Technologies (IME&T 2016) - Ubaychin A. V. Anton Viktorovich; Filatov A. Alexander; Alexeev E. Egor; Zhuk G. Gregory; Anishin M. Maxim; Gazitov S. Stanislav; Tarasov S. Sergey; Utkin B. Boris (2016, 2016)
Title screen